Development of an Augmented Reality–Based Digital Simulation Game to Enhance Students’ Empathic Character - Naini, Rohmatus; Rosada, Ulfa Danni; Rohmadheny, Prima Suci; Herdiansyah, Diki; Aditiono, Wahid; Aulia, Shazwina Syifa (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to analyze students’ levels of empathy and develop as well as evaluate the effectiveness of an Augmented Reality (AR)–integrated digital simulation game as a group guidance medium to enhance empathic character. The research employed a Research and Development (R&D) methodsing the ADDIE model, followed by an effectiveness test through a quasi-experimental design. A total of 208 students were initially screened, and 16 students with moderate empathy levels were selected and assigned equally to an experimental group and a control group. The empathy scale measured two key dimensions: cognitive empathy and emotional empathy. Data were analyzed using descriptive statistics and ANOVA to assess empathy scores, while expert and practitioner evaluations were examined using the Intraclass Correlation Coefficient (ICC) to determine the validity and consistency of the developed media. Descriptive findings showed an overall mean empathy score of 3.62 (SD = .55), with emotional empathy (M = 3.66) slightly higher than cognitive empathy (M = 3.58). The ANOVA test demonstrated a significant improvement in empathy after the intervention (F = 34.65; p = .000). These results indicate that the AR-based digital simulation game is effective in enhancing students’ empathy. The use of AR-integrated digital media in counseling services is recommended as an innovative approach to foster emotional understanding, social awareness, and empathic behavior among students.